Pemberdayaan Masyarakat Melalui Program Wakaf Al-Qur'an untuk Meningkatkan Budaya Membaca Al-Qur'an di Desa Sukarendah Kecamatan Warunggunung Kabupaten Lebak - Saepudin, Eli Apud; Febriansyah, Febriansyah; maulidah, Nasywa; Oktaviona, Angellicha Putri; Rosdiani, Rosdiani; Widia, Widia; Ikhfay, Farhan Julian; Idzhar, Ade; Yanti, Nova; Samudi, Samudi (Lembaga Teewan Journal Solutions, 2026)
The Quran “waqf’ (endowment) program is a form of community empowerment aimed at fostering a culture of Quran reading while strengthening religious life. In Sukarendah Village, Warunggunung District, Lebak Regency, there is a limited supply of Quran copies in mosques, prayer rooms (musala), and Quran Education Centers (TPQ), which impacts the community's interest in and frequency of reading the Quran. This community service initiative aims to improve public access to the Quran and cultivate a sustainable habit of reading it. The implementation employs a participatory approach involving needs assessment, coordination with village officials and religious leaders, the collection and distribution of Quran endowments, raising awareness about the importance of Quranic literacy, and providing guidance for *tadarus* (communal Quran recitation) activities. The results demonstrate increased Quran availability in places of worship and TPQs, greater community participation in Quran reading activities, and a rise in social consciousness through the endowment movement. The program also reinforces the role of the mosque as a hub for religious guidance and community education. Thus, the Quran “waqf” program has proven to be an effective community empowerment strategy for enhancing the culture of Quran reading and strengthening religious values ​​and social cohesion in Sukarendah Village.